Gamma radiation of 60Co on morphological and reproductive characteristics of M1 plants in Coffea arabica L.: Radiación gamma de 60Co en Café - Avendaño-Arrazate, Carlos H.; Gómez-Simuta, Yeudiel; Martínez-Bolaños, Misael; Méndez-López, Ismael; Ortíz-Curiel, Simitrio; Oriza-Flores, Rafael; Canul-Ku, Jaime; Reyes-López, Delfino (Ecosistemas y Recursos Agropecuarios, 2021)
Commercial coffee species have differences at the ploidy, incompatibility and autogamy level, which reduces their use for conventional genetic improvement. The present work aimed to study the radiosensitivity with gamma rays of 60Co in coffee, Oro Azteca variety, essential information to be considered in genetic improvement programs by mutagenesis. Coffee seeds var. Oro Azteca, which were irradiated with gamma rays of 60Co at doses of 0, 10, 50, 100, 200 and 300 Gy. The irradiated seeds were established in a warehouse for their germination, the M1 plants were placed in pots of 2 kg of substrate and later they were taken to a final place, distributing the treatments in an experimental design of complete random blocks with four repetitions. 15 variables were evaluated of which two were seed, eight plant and five fruit. The LD50 for percentage of germination and plant survival was calculated by exponential and quadratic regression. The GR50 was calculated for plant height and number of branches using a quadratic regression model II. In the other variables, the effect of the different radiation doses was evaluated. The LD50 for germination was 60.4 Gy and for survival 177.8 Gy. The GR50 for plant height was 120.1 Gy and for the number of branches, 107.6 Gy. For most variables, the gamma radiation of 60Co significantly decreased its values from 100 Gy.